ENSURING AN APPROPRIATE PRE-HOSPITAL RESPONSE TO PATIENTS IN SICKLE CELL CRISIS. Issue 6 (19th May 2015) - Shaw, Joanna; Fothergill, Rachael; Virdi, Gurkamal
Abstract : Introduction: Some ambulance services in the UK use the Medical Priority Dispatch System (MPDS) to triage 999 calls and determine the response allocated to patients. When MPDS was developed in the 1970s Sickle Cell Disease (SCD) was not common in the UK and was therefore not included in the system. As ethnic diversity in the UK increased so did the prevalence of SCD, yet ambulance services were still unable to identify this group of patients and assess their specific needs. Patients with SCD usually contact the ambulance service when they experience a Sickle Cell Crisis (SCC), which is characterised by severe pain. It is important ambulances arrive quickly to allow patients' pain to be managed in a timely manner. However, not having a way to identify these patients at the time of the 999 call means that patients potentially receives variable responses. Method: To determine the level of care provided, a retrospective clinical audit was undertaken for patients who reported SCC. A questionnaire was sent to patients with SCD which was used to inform the development of an override to MPDS allowing Emergency Medical Dispatchers to allocate a faster response to patients reporting SCC at the time of the 999 call. Following the introduction of the over-ride, a re-audit was conducted. Results: The re-audit showed the majority of patients (62%) received an equal or a faster response in line with the updated MPDS protocol. This increase resulted in reduced waiting time for patients; from 11 minutes and 20 seconds to 9 minutes, an average of 2 minutes and 20 seconds faster than before the over-ride. Conclusion: The over-ride resulted in a quicker ambulance response which reduced the chances of the patient's condition worsening before the arrival of an ambulance. This project also provided evidence and allowed for the SCC override to be adopted nationally.